(untitled) (Swiss Medical Weekly, 2017)
BACKGROUND Surgical aortic valve replacement (SAVR) is the treatment of choice in severe symptomatic aortic valve disease. New techniques and prostheses have been recently developed to facilitate the procedure and reduce aortic cross-clamp time (AOx). The aim of this study was to analyse the different procedural steps in order to identify the most time-consuming part during aortic clamping time and to compare impact of experience on procedural aspects. METHODS AOx during SAVR was divided into five consecutive steps. Duration of each step was measured. The first procedural step started with clamping of the aorta and ended with the beginning of the second step starting with the resection of the native aortic valve. The third step started with placement of the first valve anchoring suture, the fourth step started with tying of the first suture and the fifth and final step started after the cut of the last suture and ended with removal of the aortic clamp. Surgeons were divided into two groups based on their experience, which in our analysis was defined as a total SAVR experience of more than 100 procedures. RESULTS From March 2013 to August 2015 57 nonconsecutive patients (33% female; age, median 71.0 years, interquartile range 65.0–76.0) undergoing isolated SAVR for severe aortic valve stenosis in our institution were included in this process analysis. Two different prostheses were implanted. Forty-eight (84%) patients received a tissue valve (Perimount Magna Ease, Edwards Lifesciences, Irvine, USA) and 9 (16%) patients received a mechanical prosthesis (Medtronic AP 360, St-Paul, MN, USA). The mean estimated risk of mortality was 1.1% (0.7–1.6) according to the logistic EUROScore II. Overall duration of AOx was 50.5 ± 13.8 min, with 32.3% (16.4 ± 5.9 min) accounting for placing the sutures into the native annulus and the prosthetic sewing ring and 18.5% (9.2 ± 3.0min) accounting for tying and cutting the sutures. Surgeons with more experience performed 35 operations (61.4%) and needed an average of 44.1 ± 11.5 min versus 60.6 ± 11.0 min (p <0.001) for less experienced surgeons. Surgeons with more experience needed 14.0 ± 5.0 min for the suturing step and 8.4 ± 2.8 min for tying the sutures compared with 20.2 ± 5.2 min and 10.5 ± 3.0 min, respectively, for the less experienced surgeons with (p <0.001 and p = 0.010). CONCLUSION Placing and tying sutures in the prostheses accounts for over half (50.8%) of AOx during isolated SAVR. Experienced surgeons have significantly reduced AOx. This shortening is equally distributed between all five procedural steps.